Applications of Ion Chromatography in the Analysis of Pharmaceutical and Biological Products. - Bhattacharyya, Lokesh (John Wiley & Sons, 2012)
This is a comprehensive source of information on the application of ion chromatography (IC) in the analysis of pharmaceutical drugs and biologicals. This book, with contributors from academia, pharma, the biotech industry, and instrument manufacturing, presents the different perspectives, experience, and expertise of the thought leaders of IC in a comprehensive manner. It explores potential IC applications in different aspects of product development and quality control testing. In addition, an appendix section gives information on critical physical and chromatographic parameters related to IC.